Innovative research and development activities on high energy and high current isochronous proton accelerator. (13th March 2023) - Zhang, Tianjue; Fu, Wei; Wang, Chuan; Pei, Shilun; Yin, Zhiguo; Zhou, Hongji; Yin, Ziye; Zhang, Suping; Liu, Jingyuan; Zhu, Xiaofeng; Wang, Fei; Wang, Yang; et al.
Abstract: The MW class proton accelerators are expected to play important roles in many fields, attracting institutions to continue researching and tackling key problems. The continuous wave (CW) isochronous accelerator obtains a high-power beam with higher energy efficiency, which is very attractive to many applications. Scholars generally believe that the energy limitation of the isochronous cyclotron is ∼1 GeV. To get higher beam power by the isochronous machine, enhancing the beam focusing become the most important issue. Adjusting the radial gradient of the average magnetic field makes the field distribution match the isochronism. When we adjust the radial gradient of the peak field, the first-order gradient is equivalent to the quadrupole field, the second-order, the hexapole field, and so on. Just like the synchrotron, there are quadrupoles, hexapole magnets, and so on, along the orbits to get higher energy, as all we know. If we adjust the radial gradient for the peak field of an FFA's FDF lattice and cooperate with the angular width (azimuth flutter) and spiral angle (edge focusing) of the traditional cyclotron pole, we can manipulate the working path in the tune diagram very flexibly. During enhancing the axial focusing, both the beam intensity and the energy of the isochronous accelerator are significantly increased. Here a 2 GeV CW FFA with 3 mA of average beam intensity design is presented. It is essentially an isochronous cyclotron although we use 10 FDF lattices. The key difficulty is that the magnetic field and each order of gradient should be accurately adjusted in a large radius range. As a high-power proton accelerator with high energy efficiency, we adopt high-temperature superconducting (HTS) technology for the magnets. 15 RF cavities with a Q value of 90000 provide energy gain per turn of ∼15 MeV to ensure the CW beam intensity reaches 3 mA. A 1:4 scale, 15-ton HTS magnet, and a 1:4 scale, 177 MHz cavity have been completed. The results of such R&D will also be presented in this paper.